Climate Change Coverage in Greek Newspapers: 2001–2008. Issue 4 (4th July 2017) - Gkiouzepas, Georgios; Botetzagias, Iosif
Abstract : This paper's aim is to identify the debate and document the coverage of climate change (CC) in the Greek national press and to assess to what extent this reporting exhibits the traits anticipated by the "polarized pluralist" character of the Greek "media system." In order to do this, we analyzed articles published in three Greek quality newspapers (Kathimerini, Ta NEA, and Eleftherotypia) over the period 2001–2008 (N =2072). Our findings suggest a mixed picture: the Greek media debate is characterized by consensus on the anthropogenic causes of CC and on the promotion of renewable energy sources as a means for tackling Greek CC-related emissions. However when examining more specific/controversial CC-policy decisions, there is less evidence supporting a close link with the national character of Greek media reporting, with newspapers appearing to align themselves along partisan lines.